A newly recognized syndrome of skeletal dysplasia with opalescent and rootless teeth - Kantaputra P.N. (2014)
A Thai girl with skeletal dysplasia and dental anomalies was seen. Her anomalies consisted of disproportionately short stature, short neck, broad and depressed nasal bridge, broad chest in the anteroposterior dimension, kyphosis, widely spaced nipples, and protruded abdomen. Radiographic testing indicated that she had a large sella turcica, platyspondyly, hypoplastic acetabulum, and a small body of mandible. Both her deciduous and permanent teeth were equally opalescent, and most were rootless, with root development of the mandibular teeth more severely affected. Some maxillary roots were extremely short and tapered. Hypodontia was also observed. These findings represent a unique and hitherto undescribed syndrome of skeletal dysplasia with concomitant dental anomalies. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2001;92:303-7).